The Internet and the End of Dystopia - Andrew Feenberg (Communiquer)
Discussion of the wider implications of the Internet often situate it in relation to utopian aspirations or dystopian fears. In this paper I will attempt to break out of this by now hackneyed dilemma. The Internet does have broad implications for modern life, but neither utopia nor dystopia adequately describes it. Instead, elements of both show up as the Internet gradually matures. This is particular clear in the impact of the Internet on the public sphere. It is in this domain that something really new is happening. Exactly what is the subject of this paper.